PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN RISIKO BISNIS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR - Mnune, Tresna Dewi; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2019)
Dividend policy is related to allocation and distribution of company profits. Dividend policy is one of the financial decisions related to the policy of whether the company's profits will be paid to shareholders as dividends or retained to strengthen the capital structure. This study aimed to examine the effect on profitability, leverage, firm size and business risk to dividend policy of the company in Indonesia Stock Exchange period 2013-2017. The sample used in this study were 6 manufacturing companies listed in Indonesia Stock Exchange from the period 2013-2017 Data analysis techniques in this study uses multiple linear regression. The results show that profitability has a positive and significant effect on dividend policy, leverage has a positive and significant effect on dividend policy, firm size has a negatif and not significant effect on dividend policy and business risk has a negatif and significant effect on dividend policy. The implications of this study are expected to give consideration in making decisions by companies and shareholders about dividend policy. Keywords : profitability, leverage, firm size, business risk, dividend policy